Modeling the innate inflammatory cGAS/STING pathway: sexually dimorphic effects on microglia and cognition in obesity and prediabetes - Elzinga, Sarah E.; Koubek, Emily J.; Hayes, John M.; Carter, A.; Mendelson, Faye E.; Webber-Davis, Ian; Lentz, Stephen I.; Feldman, Eva L. (Frontiers in Cellular Neuroscience, 2023)
The prevalence of obesity, prediabetes, and diabetes continues to grow worldwide. These metabolic dysfunctions predispose individuals to neurodegenerative diseases and cognitive impairment, including dementias such as Alzheimer’s disease and Alzheimer’s disease related dementias (AD/ADRD). The innate inflammatory cGAS/STING pathway plays a pivotal role in metabolic dysfunction and is an emerging target of interest in multiple neurodegenerative diseases, including AD/ADRD. Therefore, our goal was to establish a murine model to specifically target the cGAS/STING pathway to study obesity- and prediabetes-induced cognitive impairment. We therefore performed two pilot studies in cGAS knockout (cGAS-/-) male and female mice designed to characterize basic metabolic and inflammatory phenotypes and examine the impact of high-fat diet (HFD) on metabolic, inflammatory, and cognitive parameters. cGAS-/- mice displayed normal metabolic profiles and retained the ability to respond to inflammatory stimuli, as indicated by an increase in plasma inflammatory cytokine production in response to lipopolysaccharide injection. HFD feeding caused expected increases in body weight and decreases in glucose tolerance, although onset was accelerated in females versus males. While HFD did not increase plasma or hippocampal inflammatory cytokine production, it did alter microglial morphology to a state indicative of activation, particularly in female cGAS-/- mice. However, HFD negatively impacted cognitive outcomes in male, but not female animals. Collectively, these results suggest that cGAS-/- mice display sexually dimorphic responses to HFD, possibly based on differences in microglial morphology and cognition.